2009
DOI: 10.1007/s10886-009-9683-8
|View full text |Cite
|
Sign up to set email alerts
|

Odorants that Induce Hygienic Behavior in Honeybees: Identification of Volatile Compounds in Chalkbrood-Infected Honeybee Larvae

Abstract: Social insects that live in large colonies are vulnerable to disease transmission due to relatively high genetic relatedness among individuals and high rates of contact within and across generations. While individual insects rely on innate immune responses, groups of individuals also have evolved social immunity. Hygienic behavior, in which individual honeybees detect chemical stimuli from diseased larvae and subsequently remove the diseased brood from the nest, is one type of social immunity that reduces path… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
121
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(126 citation statements)
references
References 29 publications
3
121
2
Order By: Relevance
“…To disentangle whether the observed phenomena are mainly based on differences in individual homozygosity or on differences in genetic relatedness between group members, future studies should compare colonies differing only in homozygosity or relatedness levels. Given the heritable differences in chemosensory capacities of honeybees (Gramacho & Spivak 2003;Spivak et al 2003;Swanson et al 2009), it would be highly valuable to put such future studies into a neuro-immunological framework.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To disentangle whether the observed phenomena are mainly based on differences in individual homozygosity or on differences in genetic relatedness between group members, future studies should compare colonies differing only in homozygosity or relatedness levels. Given the heritable differences in chemosensory capacities of honeybees (Gramacho & Spivak 2003;Spivak et al 2003;Swanson et al 2009), it would be highly valuable to put such future studies into a neuro-immunological framework.…”
Section: Discussionmentioning
confidence: 99%
“…Individuals may also have different thresholds to perform antiseptic behaviours (Beshers & Fewell 2001;Gramacho & Spivak 2003). A genetic basis of these traits is further corroborated by breeding experiments that allowed creating susceptible versus resistant colonies in honeybees (Rothenbuhler & Thompson 1956;Spivak & Reuter 2001;Swanson et al 2009). Furthermore, molecular studies combined with quantitative trait analyses have revealed a number of suggestive loci that influence hygienic behaviour (Lapidge et al 2002;Oxley et al 2010).…”
Section: Introductionmentioning
confidence: 99%
“…The honey bees performing hygienic behaviour are highly capable of detecting disease agents and they also uncap and remove a portion of the brood infested with the parasitic mite Varroa destructor (10)(11)(12)(13). Hygienic behaviour, in which individual honey bees detect chemical stimuli from diseased larvae and subsequently remove the diseased brood from the nest, is one type of social immunity that reduces pathogen transmission (12). Therefore, it is accepted that hygienic behaviour is the basic mechanism of resistance to diseases and pests.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have suggested that bees with the greatest olfactory sensitivity generally initiate hygienic behavior first because they can detect and accurately discriminate between abnormal and normal broods at low stimulus intensities (Martin et al, 2001;Swanson et al, 2009). Differences in olfaction may account for bee tolerance to Varroa as well as increased grooming and hygienic behavior, both of which are known to be involved in Varroa tolerance (Navajas et al, 2008).…”
Section: Discussionmentioning
confidence: 99%